Some Postwar Theoretical Trends in U.S. Archaeology - Patterson, Thomas C. (Culture, 1986)
An analysis of the theoretical tendancies of U.S. archaeology in the last forty years aims at demonstrating that archeology, as other disciplines, is closely related to broader intellectual movements or paradigms.